2019
DOI: 10.3390/rs11050587
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Estimation of Urban Waterlogging Depths from Video Images Based on Ubiquitous Reference Objects

Abstract: Video supervision equipment, which is readily available in most cities, can record the processes of urban floods in video form. Ubiquitous reference objects, which often appear in videos, can be used to indicate urban waterlogging depths. This makes video images a valuable data source for obtaining waterlogging depths. However, the urban waterlogging information contained in video images has not been effectively mined and utilized. In this paper, we present a method to automatically estimate urban waterlogging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Vision-based waterlogging depth measurement is still in the exploratory phase. To the best of our knowledge, only Chaudhary et al and Jiang et al have reported similar approaches [16,29,33]. These approaches are different to those used in traditional studies, which fetch the graduated scale data from images with a water level line, use water level sensors to monitor waterlogging depth, or use a meteorological hydrological model to simulate runoff process with remote sensing and rainfall data.…”
Section: Comparison With Existing Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…Vision-based waterlogging depth measurement is still in the exploratory phase. To the best of our knowledge, only Chaudhary et al and Jiang et al have reported similar approaches [16,29,33]. These approaches are different to those used in traditional studies, which fetch the graduated scale data from images with a water level line, use water level sensors to monitor waterlogging depth, or use a meteorological hydrological model to simulate runoff process with remote sensing and rainfall data.…”
Section: Comparison With Existing Approachesmentioning
confidence: 99%
“…Jiang et al [16,29] proposed a measurement approach to extract urban waterlogging depths from video images based on transfer learning and lasso regression. Although the approach could be used to estimate the waterlogging depth, the accuracy of the results was not high because the video images usually shoot from a fixed angle.…”
Section: Comparison With Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by the literature suggested by Referee 2, there are different ways of obtaining this information. For example, one can rely on the visibility of ubiquitous objects of known dimensions (Jiang et al 2019). This approach is limited to scenes in which such objects are visible, and fails if the reference object is hidden or partially hidden by mobile objects during a flood.…”
Section: Interactive Commentmentioning
confidence: 99%
“…We will add additional comparisons to existing methods for urban flood information extraction from surveillance images, showing both advantages and disadvantages of the alternatives. The publication of Jiang et al (2019) proposed in comment # 2.2 will be included.…”
Section: Changesmentioning
confidence: 99%